Length of Stay and 90-Day Readmission/Complication Rates in Unicompartmental Versus Total Knee Arthroplasty: A Propensity-Score-Matched Study of 10, 494 Procedures Performed in a Fast-Track Setup. (16th June 2021) - Jensen, Christian Bredgaard; Petersen, Pelle Baggesgaard; Jørgensen, Christoffer Calov; Kehlet, Henrik; Troelsen, Anders; Gromov, Kirill; Madsen, Frank; Hansen, Torben B.; Gromov, Kirill; Laursen, Mogens; Kjærsgaard-Andersen, Per; Solgaard, Soren; et al.
Abstract : Background: Whether to use unicompartmental knee arthroplasty (UKA) or total knee arthroplasty (TKA) for appropriate osteoarthritis cases is a subject of debate. UKA potentially offers faster recovery and fewer short-term complications. However, reported differences in preoperative comorbidity between TKA and UKA-treated patients could affect outcomes. The aim of this study was to investigate differences in the length of the postoperative hospital stay (LOS) as well as readmissions and complications within 90 days after surgery between matched UKA and TKA cohorts. Methods: Patients undergoing UKA or TKA in a fast-track setup at 9 orthopaedic centers from 2010 to 2017 were included in the study. Propensity score matching with exact matching for surgical year was used to address differences in demographics and comorbidity between the UKA and TKA groups, resulting in a matched cohort of 2, 786 patients who underwent UKA and 7, 708 who underwent TKA. Univariable linear or logistic regression models, multivariable mixed-effects models, and a chi-square test were used to investigate differences in LOS, readmissions, and complications between the UKA and TKA groups. Results: The UKA group had a shorter median LOS than the TKA group (1 compared with 2 days, p < 0.001). The UKA group was more likely to be discharged on the day of surgery (21.1% compared with 0.5%, odds ratio [OR] = 38.5, 95% confidence interval [CI] = 27.0 to 52.6) and less likely to have an LOS of >2 days (OR = 0.20, 95% CI = 0.17 to 0.24) compared with the TKA group. There was no difference in the 90-day readmission rate (p = 0.611) between the groups. The UKA group had fewer periprosthetic joint infections (OR = 0.50, 95% CI = 0.26 to 0.99) and reoperations (OR = 0.40, 95% CI = 0.20 to 0.81) compared with the TKA group. However, aseptic revisions were more frequent in the UKA group (OR = 2.5, 95% CI = 1.1 to 6.0). Conclusions: The UKA group had shorter hospital stays, a higher rate of discharge on the day of surgery, and fewer periprosthetic joint infections and reoperations compared with the matched TKA group. However, the TKA group had fewer aseptic revisions. Our findings support the use of UKA in a fast-track setup when indicated. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.